Effects of multielectrode renal denervation on cardiac and neurohumoral adaptations in resistant hypertension with cardiac hypertrophy: an EnligHTN I substudy. Issue 2 (February 2015) - Tsioufis, Costas; Papademetriou, Vasilios; Dimitriadis, Kyriakos; Tsiachris, Dimitris; Thomopoulos, Costas; Kasiakogias, Alexandros; Kordalis, Athanasios; Kefala, Anna; Koutra, Evagelia; Lau, Elizabeth Oi-Yan; Grassi, Guido; Stefanadis, Christodoulos
Abstract : Objective: This EnligHTN I nonrandomized substudy investigated the effect of multielectrode renal denervation (RDN) on cardiac and neurohumoral adaptations. Methods: Eighteen patients with true drug-resistant hypertension [age: 56 ± 10 years, 12 men, BMI: 33.6 ± 5.4 kg/m 2, office blood pressure (BP) by automatic device (Omron): 182 ± 19/97 ± 18 mmHg and ambulatory BP (Spacelabs): 153 ± 16/87 ± 15 mmHg receiving 4.5 antihypertensive drugs/day] and left ventricular hypertrophy underwent multielectrode RDN (EnligHTN system; St. Jude Medical), whereas 10 patients served as controls. Both groups were followed-up for 6 months. Results: Demographic data were homogenous between both patient groups. In addition to reduction of office (−42/−17 mmHg, P  < 0.001) and ambulatory (−19/−9 mmHg, P  < 0.001) BP, RDN contributed to attenuation of left ventricular mass index from 140.0 ± 17.0 g/m 2 (57.9 ± 7.9 g/m 2.7 ) to 126.7 ± 19.2 g/m 2 (52.6 ± 8.4 g/m 2.7 ) ( P  < 0.01 for both) and left atrial diameter from 42.4 ± 4.3 to 40.6 ± 3.6 mm ( P  = 0.004) at 6 months. Up to 56% of the RDN-group patients achieved a target of less than 140/90 mmHg in the office BP; proportion of RDN-group patients with concentric left ventricular hypertrophy had decreased by 39%; mitral lateral E/E′ ratio decreased from 14.8 ± 6.1 to 12.0 ± 3.2 ( P  = 0.016); isovolumic relaxation time shortened from 109.8 ± 16.2 to 100.8 ± 17.1 ms ( P  = 0.003); and N-terminal pro B-type natriuretic peptide levels reduced from 84.9 ± 35.9 to 57.2 ± 38.8 pg/ml ( P  < 0.001) significantly at 6 months post-RDN. Control patients exhibited no significant changes in all the above parameters ( P  > 0.05) at 6 months. Conclusion: Multielectrode RDN contributes to improvement of diastolic dysfunction, reduction of left ventricular mass and attenuation of NT-proBNP, suggesting additional cardiovascular benefits in drug-resistant hypertension associated with left ventricular hypertrophy.